CHILD PORNOGRAPHY - PEDOPHILIA IN THE VIRTUAL WORLD (CIPEEX, 2022)
THIS RESEARCH SEEKS TO DISCUSS CHILD PORNOGRAPHY, AS THE PEDOPHILIA IN THE VIRTUAL WORLD, IN THIS SENSE, SOME CONSIDERATIONS ARE DRAWN IN THIS SUMMARY OF THE RELATIONSHIP WITH PORNOGRAPHY AND PEDOPHILIA AND ITS HARM TO THE CHILDREN AND ADOLESCENTS WHO ARE VICTIMS OF THIS INDUSTRY. THE METHODOLOGY HERE USED WAS QUALITATIVE, USING DOCTRINES AND SCIENTIFIC ARTICLES TO DISCUSS THE THEME.